Édito - Céline Jacob; Chloé Pannier (Recherches en Éducation)
The theme of this issue explores the changes taking place in the world of education and training, and examines the workings of a changing society. This issue brings together eight contributions from the Colloque doctoral international de l'éducation et de la formation (CIDEF), held at Rennes 2 University on 20 and 21 October 2022. The contributions diverge in terms of the contexts in which they are set, the different actors involved and the diversity of the methodologies used. Nevertheless, what the articles selected have in common is that they question and analyse the effects of transitions and, more generally, of the changing society on the actors on the one hand, but also on what the actors do with them on the other. The first part sheds light on the way in which individuals negotiate change as part of collective dynamics both inside and outside the school. The second part looks at how teachers experience change. Finally, the third part focuses on the way in which players deal with these transitions through artefacts or institutional injunctions.